Flower production prospects and sustainability challenges in Ethiopia: A systematic review - Mebrat, Shiferaw; Degwale, Alemu; Mekonen, Temesgen; Mebrat, Amare (Frontiers in Environmental Science, 2022)
As a result of its rapid economic growth, diversification of export products, employment opportunities, and foreign exchange earnings, floriculture is a crucial industry in Ethiopia. Alarms have been raised recently, nevertheless, as the industry significantly damages both the environment and societal well-being. Consequently, corporate social responsibility, which strikes a balance between the three Ps of profit, planet, and people, has emerged as a novel concept in ethical business governance systems to effectively address societal and environmental concerns. In Ethiopia, this concern for sustainability is in its infancy. Therefore, it is crucial for the industry to examine the current findings with regard to floriculture sustainability and explain the apparent discrepancies. As a result, systematic review was conducted with the aim to analyze the sustainability challenges in the floriculture business and its impact on the environment and society, as well as, the measures that should be made for the sector to develop in a way acceptable to the nation. Accordingly, 29 papers from various sources (government reports and websites) and 59 articles from databases (Web of Science, Science Direct, PubMed, and Google Scholar) were chosen for synthesis. The sustainability challenges were analyzed and addressed in this article along with various theoretical and practical examples. The effects of unsustainable flower farming on people, the health of the soil, and the quality of the water are also covered. The paper adds to the scientific discussion by pointing out the areas that need further study and the policy ramifications of sustainability in the flower business.